Talking Difference : On Gender and Language. - Crawford, Mary (Gender and Psychology series., 1995)
'Talking Difference provides an excellent critical review of a good selection of the research in language and gender published over the last 20 years, including a substantial amount from the area of psychology ... I found this an exhilarating book, written with energy and wit. Crawford maintains a consistently critical approach, identifying contradictions and ambiguities in popular theories of gender difference, and exposing conceptual and methodological weaknesses in language and gender research. The volume is well-structured and readable; it will prove very valuable in und.